STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI KOMUNIKASI PERSUASIF - Shelty D.M Sumual; Henny Tambingon; Ayu Lestari; Glorya Walewangko (Jurnal Genta Mulia, 2024)
This research was carried out at SMA Negeri 7 Manado, with the aim of finding out the persuasive communication strategies used to increase students' learning motivation at school. In this research, a case study and a descriptive qualitative approach were used. This research was carried out by collecting data through observing research objects and interviewing related informants. This research shows that communication, whether personal from teachers to students, or guardians/parents to students, has a significant impact on the students' learning motivation. This personal communication approach must be maintained in the sense that it can be carried out continuously so that good relationships can be established between teachers, students and guardians/parents.